Development of Ethnoscience-Based Learning on Bugis Traditional Food in The 4th Grade IPAS Textbook in Elementary Schools - Adela, Dhea; Suprapmanto, Joko; Sehab, Nurhayati (Jurnal Paedagogy, 2025)
This research aims to develop a textbook based on local wisdom with an integration of ethnoscience learning about traditional Bugis food. This research used Research and Development with a 4D model which consists of four stages, namely define, design, develop and disseminate. The research subjects for the practicality test included 192 students of IV grade elementary school and 6 teachers from the school population in Pallangga District, Gowa Regency, South Sulawesi. The validity test of textbooks was judged by material experts, language experts and media experts. Based on the results of the analysis of the Gregory formula, it is stated that the validation coefficient for learning books by material experts, media experts and language experts was 1.00 with the content validity category being "very high". The results of the textbook validation received a very high assessment and were categorized as valid because the contents of the textbook were in accordance with the competencies and indicators that must be achieved by fourth grade elementary school students. This is demonstrated by the accuracy, completeness and suitability of the core material and supporting material according to student characteristics. The average teacher response to textbooks was 95% in the "very practical" category and the average student response was 92%. In the Ease of Use (navigation) aspect, the textbook ease indicator reached an average value of 0.89 or 89%. These results showed that students did not experience difficulties in using the science and technology textbook based on local Bugis traditional wisdom because the instructions in the book are clear.